Drugging conformational states of GPCRs - Kolb, Peter (Henry Stewart Talks, 2021)
Structure-based drug design, GPCRs and their conformational spectrum, Docking to find selective ligands and ligands with tailored efficacy, Expanding chemical space to address different GPCR conformations